Role of Latex particle agglutination test in the diagnosis of meningitis - Begum, Nurjahan; Ahmed, Iftikhar; Salam, Md. Abdus; Begum, Shahanara; Alam, KM Faisal (Bangladesh Society of Medical Microbiologists, 2007)
A total of 45 clinically suspected cases of meningitis of all ages, admitted at Rajshahi Medical College Hospital (RMCH), were studied to find out the etiological agents of meningitis. Among the cases, 32 (7l.1oh) were diagnosed as aseptic meningitis and L3 (ZS.Sgoh) as bacterial meningitis by the conventional CSF study. But out of total 45 cases, lg (40oh) were diagnosed as bacterial meningitis by Latex particle agglutination test (LPAT). The LPAT is widely used in clinical microbiology laboratories and can be considered as an important supplement to the culture and Gram stain of CSF specimens. Rapid antigen detection tests may provide positive results when culture and Gram stain results are negative for meningitis patients who have received antimicrobial therapy. So, in our country, where empirical broad-spectrum antibiotic is randomly used, LPAT may be considered as an adjunct to establish the diagnosis of bacterial meningitis